Lung cancer vaccine strategies: exploring the spectrum from traditional to RNA-based platforms - Pazoki, Alireza; Dadfar, Sepehr; Alirezaee, Atefe; Oksenych, Valentyn; Haghmorad, Dariush (Frontiers in Bioengineering and Biotechnology, 2025)
Lung cancer continues to be a leading cause of cancer-related mortality worldwide, with survival rates stubbornly low despite significant advancements in conventional therapies. The limited effectiveness of traditional immunotherapies, particularly in advanced stages of the disease, highlights an urgent need for innovative treatment options. Cancer vaccines represent a promising Frontier in this battle, aiming to harness the power of the immune system to create lasting memory against tumor cells. This approach not only promotes tumor regression but also does so with minimal adverse effects. The death of tumor cells induced by these vaccines triggers a cascade of immune responses, activating functional T cells and sustaining the cancer-immunity cycle. Among emerging platforms, RNA-based vaccines have garnered particular attention for their rapid development potential, flexible design, and ability to induce robust cellular and humoral immunity. As a result, cancer vaccines—including RNA-based modalities—are increasingly viewed as a groundbreaking therapeutic strategy in the immunotherapy landscape for solid tumors. In this review, we examine recent advancements in lung cancer vaccines, focusing on antigen selection, innovative vaccine platforms and delivery strategies. Moreover, we provide a detailed analysis of ongoing and completed clinical trials, including targeted antigens, administration routes, and platforms used. Additionally, we discuss the potential benefits of combination therapies to enhance vaccine efficacy and address the limitations of these vaccines. Our goal is to provide a comprehensive overview of how these developments aim to overcome current treatment challenges and improve patient outcomes.